Self-efficacy in product development student teams - what shapes students’ perceived self-efficacy - Martti Jerkku; Ville Taajamaa; Senni Kirjavainen (United Kingdom, 2022)
This paper aims to provide a perspective of the student´s perceived self-efficacy in a team
based project course where students face open-ended, ill-defined problems. We discuss the
development of self-efficacy in the team members and how different situations and events
affect their perceived self-efficacy. The data used in this paper was gathered through
interviews from students taking a yearlong masters´ level capstone course. Results of the
study show that the students’ overall self-efficacy increased most in team-based moments. We
show also how entrepreneurial self-efficacy of students can be enhanced during problembased
New Product Development process. Finally we will conclude the potential of the
researched course to provide practical experiences of project work as well as its potential for
delivering entrepreneurial skills for the students during their education.
Proceedings of NordDesign 2016, Volume 2, Trondheim, Norway, 10th - 12th August 2016